Evaluasi pemeliharaan lanskap terhadap kapasitas tenaga kerja di trans studio mall bandung - Dewi Sartika Nusye; Huda Nurjanti; Ika Kusmawati (Composite : Jurnal Ilmu Pertanian, 2024)
Landscape maintenance work is part of landscape work that focuses on daily activities to maintain the quality of beauty, environment, health, and plant growth in a landscape. Landscape maintenance at Trans Studio Mall Bandung is included in operational work that aims to increase the selling value of the mall landscape area, if the work is carried out in accordance with the capacity and work program that has been determined. Trans Studio Mall Bandung is an international standard shopping center that has green open space in its area. The green open space is managed by the Landscape Maintenance Unit (UPL) of Trans Studio Mall. To evaluate the landscape maintenance at Trans Studio Mall, a study will be conducted on the capacity of each type of maintenance work throughout the landscape area. The evaluation of maintenance work that will be discussed includes daily routine work carried out by the gardener. The studies start from preparation, data collection, analysis, and synthesis. Data was collected through observation, interviews, and literature studies, then analyzed qualitatively and quantitatively. The results obtained show that the number of workers still does not meet the minimum capacity for landscape maintenance at Trans Studio Mall.